The Demand for Credit Union Shares: A Cross-Sectional Analysis - Taylor, Ryland A. (Journal of Financial and Quantitative Analysis, 1972)
Many recent studies of the demand for financial assets have been of an aggregative nature, using time-series data. However, some efforts to disaggregate and rely more heavily on cross-sectional data have yielded substantial improvements in discovering relationships not evident due to aggregation. The purpose of this paper is to continue in this spirit of disaggregation and to estimate the demand for one homogeneous type of financial asset, credit union shares, on a cross-sectional basis.